(untitled) (Journal of Medicine, 2025)
Migrant women ventured overseas to work in domestic roles and came back to their home countries enduring different types of physical and psychological mistreatment. Among those who faced various forms of mistreatment during their migration, a significant number experienced mental health issues upon returning home. An example is a 28-year-old female migrant who was physically abused in Saudi Arabia and later developed psychosis after coming back home. This case study provides a detailed understanding of the observation process, highlighting that female migrants who return home encounter diverse forms of social harassment and stigma, such as social isolation, excessive anxiety, depression, fear, and loss of dignity. Consequently, the report recommends the expansion of mental health services and rehabilitation programs for female migrants upon their return. J MEDICINE 2025; 26: 59-62